2008
DOI: 10.1111/j.1745-7254.2008.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endogenous sulfur dioxide on monocrotaline-induced pulmonary hypertension in rats1

Abstract: Aim: The present study aimed to explore the protective effect of endogenous sulfur dioxide (SO 2 ) in the development of monocrotaline (MCT)-induced pulmonary hypertension (PH) in rats. Methods: Forty Wistar rats were randomly divided into the MCT group receiving MCT treatment, the MCT+L-aspartate-β-hydroxamate (HDX) group receiving MCT plus HDX treatment, the MCT+SO 2 group receiving MCT plus SO 2 donor treatment, and the control group. Mean pulmonary artery pressure (mPAP) and structural changes in pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 43 publications
2
61
0
Order By: Relevance
“…[49][50][51] Furthermore, HDX could inhibit AAT activities and the generation of endogenous SO 2 in both pulmonary tissues and myocardium. 17,18,36 The present results showed that compared with vehicle-treated cells, OA induced a marked reduction of SO 2 generation but a significant increase in O 2 À and OH À generation, which could be reversed by supplementation of SO 2 . HDX-treated cells generated significantly increased oxygen radicals and markedly upregulated caspase-3 cleavage and PARP expression, resulting in cell injury and apoptosis demonstrated by TUNEL and Hoechst staining.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…[49][50][51] Furthermore, HDX could inhibit AAT activities and the generation of endogenous SO 2 in both pulmonary tissues and myocardium. 17,18,36 The present results showed that compared with vehicle-treated cells, OA induced a marked reduction of SO 2 generation but a significant increase in O 2 À and OH À generation, which could be reversed by supplementation of SO 2 . HDX-treated cells generated significantly increased oxygen radicals and markedly upregulated caspase-3 cleavage and PARP expression, resulting in cell injury and apoptosis demonstrated by TUNEL and Hoechst staining.…”
Section: Discussionmentioning
confidence: 55%
“…14 Endogenous SO 2 protects against isoproterenol-induced myocardial injury and increases myocardial antioxidant capacity in rats, 18 and might play a protective role in the pathogenesis of monocrotalin-induced pulmonary hypertension and promote endogenous antioxidative capacities, 36 suggesting that endogenous SO 2 was involved in the regulation of cardiovascular oxidative stress. 37 Regardless of recent research on the emerging protective role of endogenous SO 2 in maintaining homeostasis in vivo, little has been revealed To examine the role of the endogenous SO 2 /AAT1/AAT2 pathway in the development of ALI, we established a rat model of OA-induced ALI and determined the level of endogenous SO 2 /AAT1/AAT2 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The major pathways for the disposal of H 2 O 2 in cells are catalyzed by GSH-Px and catalase, which metabolize H 2 O 2 into water and oxygen. Du and coworkers 41 reported that endogenous SO 2 raised the antioxidant capacity in rats of monocrotaline-induced pulmonary hypertension. In this study, antioxidant activity demonstrated by SOD and GSH-Px in the myocardial tissue of ISO-treated rats decreased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood PMN cell culture and evaluation of PMN apoptosis by FCM Peripheral blood PMNs were cultured in RPMI-1640 medium at 37 °c in 5% cO 2 and treated with 30 mg/L LPS and different concentration of SO 2 (10,20, and 30 µmol/L SO 2 ) in vitro for 6 h for the detection of apoptosis-related protein expression using the Western blotting method. To determine the rate of apoptosis, PMNs were cultured for 24 h and then submitted to FCM.…”
Section: Isolation and Purification Of Peripheral Blood Pmnsmentioning
confidence: 99%
“…SO 2 was also previously considered a risk factor for respiratory and cardiovascular disease [9] . Recently, studies have shown that SO 2 plays important pathophysiologic roles during many disease processes, including the attenuation of monocrotaline-induced pulmonary hypertension, the inhibition of hypoxic pulmonary vascular structural remodeling, protection against isoproterenol-induced myocardial injury, and the increase of myocardial antioxidant capacity [10][11][12] . However, the effects of SO 2 on ALI and its mechanisms are poorly understood.…”
Section: Introductionmentioning
confidence: 99%